Gennadiy Harlampievich Gruntovskiy - Staff of SI «SISJP NAMS», - (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
The article is devoted to the memory of the famous scientist, doctor, public figure, doctor of medical sciences professor Gruntovsky Gennady Kharlampievich.